2004
DOI: 10.1137/s0097539703435522
|View full text |Cite
|
Sign up to set email alerts
|

A Characterization of Universal Stability in the Adversarial Queuing Model

Abstract: We study universal stability of directed and undirected graphs in the adversarial queuing model for static packet routing. In this setting, packets are injected in some edge and have to traverse a predefined path before leaving the system. Restrictions on the allowed packet trajectory provide a way to analyze stability under different packet trajectories. We consider five packet trajectories, two for directed graphs and three for undirected graphs, and provide polynomial time algorithms for testing universal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 20 publications
1
35
1
Order By: Relevance
“…They showed the existence of an acknowledgment based protocol that has fair latency for injection rates at most 1 cn lg 2 n , for some c > 0, and developed an explicit acknowledgment based protocol that has fair latency for injection rates at most 1 27n 2 ln n . Finally, they showed that no acknowledgement-based protocol is stable for injection rates larger than 3 1+lg n . Algorithmic problems not regarding pure communication issues in distributed environments relying on multiple access channels have been also studied in the literature.…”
Section: Related Workmentioning
confidence: 99%
“…They showed the existence of an acknowledgment based protocol that has fair latency for injection rates at most 1 cn lg 2 n , for some c > 0, and developed an explicit acknowledgment based protocol that has fair latency for injection rates at most 1 27n 2 ln n . Finally, they showed that no acknowledgement-based protocol is stable for injection rates larger than 3 1+lg n . Algorithmic problems not regarding pure communication issues in distributed environments relying on multiple access channels have been also studied in the literature.…”
Section: Related Workmentioning
confidence: 99%
“…The subfield of proposing a characterization for universally stable networks was first initiated in [3,6] proving that certain well-known network topologies (DAGs, trees, ring) are universally stable. These results were significantly improved by Gamarnik [10] presenting a tight characterization of stable topologies for undirected graphs and by Goel [11] and Alvarez et al [2] proving a tight characterization of stable topologies for directed graphs.…”
Section: Related Workmentioning
confidence: 94%
“…They proved that many 2 NTS gives priority to the nearest packet to its origin in the network. 3 FTG gives priority to the furthest packet from its destination in the network.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, those results concerning universal stability can be transferred from one model to the other. Therefore, according to the results in [1] and [2], we can state the following, Corollary 1 Directed acyclic graphs and rings are universally stable in the ½ model. …”
Section: The ½ Modelmentioning
confidence: 85%
“…On the contrary, the main goal of the model is to study conditions for stability of the network under different protocols. A considerable amount of results is available nowadays (see, e.g., [9,3,11,2,17,14,18,1,8,12,16,2]). …”
Section: Introductionmentioning
confidence: 99%